Dental Tissue-Derived Human Mesenchymal Stem Cells and Their Potential in Therapeutic Application - Lu Gan; Ying Liu; Dixin Cui; Yue Pan; Liwei Zheng; Mian Wan (Hindawi Limited, 2020)
Human mesenchymal stem cells (hMSCs) are multipotent cells, which exhibit plastic adherence, express specific cell surface marker spectrum, and have multi-lineage differentiation potential. These cells can be obtained from multiple tissues. Dental tissue-derived hMSCs (dental MSCs) possess the ability to give rise to mesodermal lineage (osteocytes, adipocytes, and chondrocytes), ectodermal lineage (neurocytes), and endodermal lineages (hepatocytes). Dental MSCs were first isolated from dental pulp of the extracted third molar and till now they have been purified from various dental tissues, including pulp tissue of permanent teeth and exfoliated deciduous teeth, apical papilla, periodontal ligament, gingiva, dental follicle, tooth germ, and alveolar bone. Dental MSCs are not only easily accessible but are also expandable in vitro with relative genomic stability for a long period of time. Moreover, dental MSCs have exhibited immunomodulatory properties by secreting cytokines. Easy accessibility, multi-lineage differentiation potential, and immunomodulatory effects make dental MSCs distinct from the other hMSCs and an effective tool in stem cell-based therapy. Several preclinical studies and clinical trials have been performed using dental MSCs in the treatment of multiple ailments, ranging from dental diseases to nondental diseases. The present review has summarized dental MSC sources, multi-lineage differentiation capacities, immunomodulatory features, its potential in the treatment of diseases, and its application in both preclinical studies and clinical trials. The regenerative therapeutic strategies in dental medicine have also been discussed.